VPS18-regulated vesicle trafficking controls the secretion of pectin and its modifying enzyme during pollen tube growth in Arabidopsis. Issue 9 (14th June 2021) - Hou, Saiying; Shi, Jiao; Hao, Lihong; Wang, Zhijuan; Liao, Yalan; Gu, Hongya; Dong, Juan; Dresselhaus, Thomas; Zhong, Sheng; Qu, Li-Jia
Abstract: In eukaryotes, homotypic fusion and vacuolar protein sorting (HOPS) as well as class C core vacuole/endosome tethering (CORVET) are evolutionarily conserved membrane tethering complexes that play important roles in lysosomal/vacuolar trafficking. Whether HOPS and CORVET control endomembrane trafficking in pollen tubes, the fastest growing plant cells, remains largely elusive. In this study, we demonstrate that the four core components shared by the two complexes, V acuole p rotein s orting 11 (VPS11), VPS16, VPS33, and VPS18, are all essential for pollen tube growth in Arabidopsis thaliana and thus for plant reproduction success. We used VPS18 as a representative core component of the complexes to show that the protein is localized to both multivesicular bodies (MVBs) and the tonoplast in a growing pollen tube. Mutant vps18 pollen tubes grew more slowly in vivo, resulting in a significant reduction in male transmission efficiency. Additional studies revealed that membrane fusion from MVBs to vacuoles is severely compromised in vps18 pollen tubes, corroborating the function of VPS18 in late endocytic trafficking. Furthermore, vps18 pollen tubes produce excessive exocytic vesicles at the apical zone and excessive amounts of pectin and pectin methylesterases in the cell wall. In conclusion, this study establishes an additional conserved role of HOPS/CORVET in homotypic membrane fusion during vacuole biogenesis in pollen tubes and reveals a feedback regulation of HOPS/CORVET in the secretion of cell wall modification enzymes of rapidly growing plant cells. Abstract : Arabidopsis VPS18 plays an important role in regulating pollen tube growth through mediating the late endocytic trafficking and secretion of pectin and associated enzymes to the cell wall.